POLA ASUH DEMOKRATIS ORANGTUA KRISTEN DALAM PEMBENTUKAN KARAKTER REMAJA - Andrianus Nababan (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Indonesia, 2020)
Christian parents' democratic parenting patterns contribute significantly to the formation of a teenager’s character based on the Christian values and norms applied in society. Ironically, some Christian parents tend to lack understanding and do not apply the democratic parenting style well. Consequently, teenagers behave out of Christian values. According to this literature review, some characteristics of Christian parents’ democratic style was identified, namely: (1) making regulations together, and then carry them out; (2) providing guidance based on the God’s words; (3) creating the harmony of the family; (4) involving the teenager in various matters; (5) giving teenager freedom to express his/her opinions; (6) supervising the teenager without rigidity. In order to develop Christian parents' democratic parenting patterns, further research is needed. Keywords: Character building, Christian parents, democratic parenting, Teenager